Utilization and Rationalization of TikTok Application for Hospital Health Promotion During Covid-19 Pandemic - Arti INDIRA (Indonesia Strategic Sustainability, 2023)
In the midst of the limitations of people's movements during the Covid-19 Pandemic, the role of technology is increasingly important and has now changed the order of life. The Health Sector, in this case the hospital, has made various adaptation efforts during the pandemic, one of which is optimizing the use of digital media to convey health information, provide education, and communicate with the public. Many studies on social media There are not many studies on the use of the TikTok application for hospital health promotion during the COVID-19 pandemic. The purpose of this study was to analyze the utilization and rationalization of the use of the TikTok application for hospital health promotion during the COVID-19 pandemic. The Systematic Review approach was carried out based on the Preferred Guide to Reporting Items for Systematic Review and Meta-analysis (PRISMA). In addition, the advantages of TikTok were found as a medium for hospital health promotion. The use of Tik Tok, which is currently popular culture in Indonesia, can be a medium for Hospital Health Promotion during the COVID-19 Pandemic which is quite ideal. This is due to popular culture that does not look at social strata so that it is easier to reach the wider community, further studies are needed, especially surveys related to content related to the types and characteristics of health promotion of various types of hospitals in Indonesia.